The Effect Of Environmental Social Governance (Esg) Disclosure On Company Financial Performance With Company Size As A Moderating Variable - Arfiyan, Islam Samodra; Atmini, Sari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to analyze and obtain empirical evidence on the impact of Environmental, Social, and Governance (ESG) disclosure on companies' financial performance, utilizing firm size as a moderating variable. The research population comprises companies from the infrastructure, energy, industrials, basic materials, and properties & real estate sectors listed on the Indonesia Stock Exchange during the 2018-2022 period, totaling 408 companies. This study employs simple linear regression and Moderating Regression Analysis methods. The findings indicate that ESG disclosure has a negative effect on companies' financial performance. The moderation results reveal that firm size attenuates the negative impact of ESG disclosure on financial performance. Further analysis uncovers that ESG disclosure has a significantly positive effect on companies' financial performance two periods after disclosure, despite firm size weakening the relationship between ESG disclosure and financial performance. The implications of this study demonstrate that increased ESG disclosure leads to higher costs incurred by the company, thereby reducing financial performance. In the long term, two periods following ESG disclosure, the company receives favorable evaluations from stakeholders and gains legitimacy from society, resulting in improved financial performance.